A redescription of Hypogastrura gisini Strenzke, 1954 (Collembola: Hypogastruridae) and description of a new related species from Crete (Greece) - Skarżyński, Dariusz; Gwiazdowicz, Dariusz J. (Zootaxa, 2022)
Hypogastrura gisini Strenzke, 1954 is redescribed based on paratypes and other available material. A description of similar new species from Crete‒‒H. cretensis sp. nov., formerly known as H. cf. gisini sensu Ellis (1976), is also provided. Both species belong to the manubrialis group and resemble H. breviempodialis (Stach, 1949), H. tianshanica Martynova, 1970 and H. ubsunurensis Babenko, 1999, which have a retinaculum with 3 + 3 teeth and a maxillary head of the H. vernalis type. H. gisini has a unique combination of morphological characters: claws without inner tooth, empodium shorter than half inner edge of claw, without basal lamella and setae m1 on abdominal tergum V usually absent. This species prefers sandy habitats on the shores of the Baltic Sea, Kattegat, North Sea, Black Sea and Mediterranean Sea. H. cretensis sp. nov. can be distinguished from its congeners by a combination of the following features: claws with small inner tooth, empodium with basal lamella equal to or slightly longer than half of the inner edge of claws and setae m1 on abdominal tergum V usually present. The new species seems to be associated with anthropogenic habitats mainly (e.g. roadsides, orchards, meadows) in the interior of Crete.